Bilateral Pseudoarthrosis of the Medial End of the Clavicles: A Rare Case Report with a Two-Year Follow-Up - Manuel Bomfim Braga Júnior; Argos Queiroz Alves de Souza; Carlos Augusto Belchior Bitencourt Júnior; Fernando Henrique Uchôa de Alencar; Renan Teixeira Lôbo; Jonatas Brito de Alencar Neto; Réjelos Charles Aguiar Lira (Case Reports in Orthopedics)
Bilateral clavicle fractures are considered rare. Most of the cases are caused by high energy traumas, such as automobile accidents. Such fracture is related to a higher frequency and severity of associated lesions. In this report, the authors present a twenty-two-year-old male patient’s case who, after a motorcycle collision, suffered a bilateral medial end clavicle closed fracture, developing asymptomatic bilateral pseudoarthrosis after the patient refuses surgical treatment. The presented case is quite rare. Aspect related to the patient’s evolution during treatment will be discussed, plus the fracture mechanism, associated injuries, the bilateral clavicular fractures treatment, and management in cases of pseudoarthrosis will be analyzed.